Author Correction: Improved genome recovery and integrated cell-size analyses of individual uncultured microbial cells and viral particles - Ramunas Stepanauskas (Nature Portfolio, 2017)
The original version of this Article contained errors in the units of concentration of three reagents listed in the Methods. These errors have all been corrected in both the PDF and HTML versions of the Article.